2020
DOI: 10.13057/biodiv/d210654
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity, population structure, and regeneration status of trees in Fakim Wildlife Sanctuary, Nagaland, Northeast India

Abstract: Abstract. Ao A, Changkija S, Tripathi SK. 2020. Species diversity, population structure, and regeneration status of trees in Fakim Wildlife Sanctuary, Nagaland, Northeast India. Biodiversitas 21: 2777-2785. The plant species composition and diversity represent the overall health of the forest ecosystems and provide useful insight on forest conservation, and the species regeneration is important in assessing the potential of the forests to serve the society on sustained basis. This present study aimed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The small size (≤9.5 cm class) showed the highest tree density but then declined as the bigger size class increased. The results are consistent with previous reports that tree density decreased from smaller to bigger size classes (Ao et al 2020;Rawal and Subedi 2022). The number of species and Shannon diversity index (Figure 2B-C) drastically decreased from small to bigger dbh class in all forests.…”
Section: Size Class Distributionsupporting
confidence: 93%
“…The small size (≤9.5 cm class) showed the highest tree density but then declined as the bigger size class increased. The results are consistent with previous reports that tree density decreased from smaller to bigger size classes (Ao et al 2020;Rawal and Subedi 2022). The number of species and Shannon diversity index (Figure 2B-C) drastically decreased from small to bigger dbh class in all forests.…”
Section: Size Class Distributionsupporting
confidence: 93%
“…Whitmore (1990) has also recorded patchy ground flora distribution in most tropical rainforests. The dominance of families like Fagaceae, Lauraceae, Euphorbiaceae, Myrtaceae, and Rubiaceae in the study area is similar to the tropical rain forests of Pasoh reserve forests in Malaysia, tropical wet evergreen forests, Western Ghats (Giriraj et al 2008), the wet temperate forest of Nagaland (Ao et al 2020) and sub-tropical forests/sacred forests in Meghalaya (Manokaran et al 1990;Mishra et al 2004;Tripathi and Khongjee 2010;. One of the unique features of the sub-tropical evergreen forests of southern Meghalaya is the presence of Fagaceae as one of the dominant families with 11 species.…”
Section: Discussionmentioning
confidence: 59%
“…That may be considered moderate as compared to species richness in neo-tropical forests, which ranges from 20 species ha -1 in the Varzea forest of Rio Xingu, Brazil (Campbell et al 1992) to 307 species ha -1 in the Amazonian Equator (Valencia et al 1994) and other tropical forests where it ranged from 26 species ha -1 in Kolli hills of India (Chittibabu and Parthasarathy 2000) to 231 species ha -1 in Brunei Darussalam of Southeast Asia (Poulsen et al 1996) and 76 species ha -1 recorded in evergreen tropical forests, Meghalaya ). However, it may be considered as considerably higher when compared to other sites in southern and central Western Ghats, viz., 30 species ha -1 in Nelliampathy (Chandrashekara and Ramakrishnan 1994), 57 species ha -1 in Mylodai forest of Courtallum (Parthasarathy and Karthikeyan 1997), 60 species ha -1 recorded in the wet temperate forest of Fakim Wildlife Sanctuary, Nagaland, India (Ao et al 2020), and 75 species ha -1 recorded in the tropical dry deciduous forest of the Eastern Ghats, India (Gandhi and Sundarapandian 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, information reported that these forest regions are characterized by high rainfall, humidity and favourable temperature. The previous studies reported that species diversity is based on the species richness and evenness (Ao et al, 2020), and the richness in-creasing from the pole to equator (Roy et al, 2004). Thus, the floristic composition of the vegetation changes gradually due to forest degradation and recovering during the course of succession (Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 98%